Designing The Room 19 Mascot as a Promotional Strategy Medium - Shafira Nursyah Putri; Didit Widiatmoko Soewardikoen; Hanif Azhar; Mahendra Nurhadiansyah (Publikasi Indonesia, 2024)
The rapid development of technology has led to innovations such as library cafes, which aim to promote literacy among young people. However, the concept of library cafes is still not widely known. This research explores the effectiveness of using a mascot as a promotional strategy to enhance public awareness of The Room 19 library cafe and encourage reading interest. The study employed interviews, observations, questionnaires, and literature reviews for data collection. The findings show that the mascot, designed with an approachable and creative visual identity, effectively increases the visibility of The Room 19 among students and young professionals. The mascot represents the library cafe's brand values and creates an emotional connection with the target audience. In conclusion, using a mascot as a promotional medium has significant potential to foster literacy promotion and establish a stronger relationship with the community through engaging branding efforts.